2006
DOI: 10.1021/bi051913e
|View full text |Cite
|
Sign up to set email alerts
|

Size and Orientation of the Lipid II Headgroup As Revealed by AFM Imaging

Abstract: In this study, we investigated the size and orientation of the bacterial Lipid II (L II) headgroup when the L II molecule is present in liquid-crystalline domains of DOPC in a supported DPPC bilayer. Using atomic force microscopy, we detected that L II causes the appearance of a 1.9 nm thick layer, situated over the DOPC headgroup region. With an increased scanning force, this layer can be penetrated by the AFM tip down to the level of the DOPC bilayer. Using different L II precursor molecules, we demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 32 publications
10
33
0
Order By: Relevance
“…Interestingly, it has been shown that fluorescently labeled vancomycin, which binds lipid II, localizes to the strongly fluorescent membrane patches induced by daptomycin (22), indicating the presence of lipid II in these arrested fluid lipiddaptomycin clusters. Lipid II is likely to accumulate at RIFs, because its long bactoprenol moiety prefers a fluid lipid environment (56). These observations are in good agreement with our finding that MurG preferentially binds to RIFs and further supports the notion that RIFs are membrane microdomains associated with lateral cell wall biosynthesis (38,57,58).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, it has been shown that fluorescently labeled vancomycin, which binds lipid II, localizes to the strongly fluorescent membrane patches induced by daptomycin (22), indicating the presence of lipid II in these arrested fluid lipiddaptomycin clusters. Lipid II is likely to accumulate at RIFs, because its long bactoprenol moiety prefers a fluid lipid environment (56). These observations are in good agreement with our finding that MurG preferentially binds to RIFs and further supports the notion that RIFs are membrane microdomains associated with lateral cell wall biosynthesis (38,57,58).…”
Section: Discussionsupporting
confidence: 90%
“…Incorporation of Lipid II in supported bilayers of phosphatidylcholine revealed that the bactoprenol chain must be fluid, because Lipid II partitions in fluid domains, present in mixed solid/fluid bilayers. This was observed by atomic force microscopy (AFM) using the lantibiotic nisin, which binds specifically to Lipid II to visualize its location [3]. Consistent with this finding was the observation made by confocal fluorescence microscopy that NBD-labeled Lipid II was homogeneously distributed in GUVs of DOPC [4].…”
Section: Lipid II Occurrence and Propertiessupporting
confidence: 61%
“…The AFM technique also revealed that the head group of Lipid II is soft and can be penetrated by the AFM probe [3]. This property of the molecule allowed insight into the dimensions of the head group, which was estimated to be 1.9 nm high as compared to the level of the phospholipid head group [3].…”
Section: Lipid II Occurrence and Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, E. coli minicells, in which a very high percentage of the membrane is in a highly curved state, are enriched in cardiolipin (Koppelman et al, 2001). Thus, the effect of membrane composition on cell shape might be indirect, such as by affecting the localization of lipid II or MreB, which are both linked to specific membrane organization (Ganchev et al, 2006; Strahl et al, 2014). …”
Section: Generation Of Cell Shapementioning
confidence: 99%